Azure DevOps Explained - Zaal, Sjoukje; Demiliani, Stefano; Malik, Amit (Packt Publishing, 2020)
Implement real-world DevOps and cloud deployment scenarios using Azure Repos, Azure Pipelines, and other Azure DevOps tools Key Features Improve your application development life cycle with Azure DevOps in a step-by-step manner Apply continuous integration and continuous deployment to reduce application downtime Work with real-world CI/CD scenarios curated by a team of renowned Microsoft MVPs and MCTs Book Description Developing applications for the cloud involves changing development methodologies and procedures. Continuous integration and continuous deployment (CI/CD) processes are a must today, but are often difficult to implement and adopt. Azure DevOps is a Microsoft Azure cloud service that enhances your application development life cycle and enables DevOps capabilities. Starting with a comprehensive product overview, this book helps you to understand Azure DevOps and apply DevOps techniques to your development projects. You'll find out how to adopt DevOps techniques for your development processes by using built-in Azure DevOps tools. Throughout the course of this book, you'll also discover how to manage a project with the help of project management techniques such as Agile and Scrum, and then progress toward development aspects such as source code management, build pipelines, code testing and artifacts, release pipelines, and GitHub integration. As you learn how to implement DevOps practices, this book will also provide you with real-world examples and scenarios of DevOps adoption. By the end of this DevOps book, you will have learned how to adopt and implement Azure DevOps features in your real-world development processes. What you will learn Get to grips with Azure DevOps Find out about project management with Azure Boards Understand source code management with Azure Repos Build and release pipelines Run quality tests in build pipelines Use artifacts and integrate Azure DevOps in the GitHub flow Discover real-world CI/CD scenarios with Azure DevOps Who this book is for This book is for developers, solutions architects, and DevOps engineers interested in getting started with cloud DevOps practices on Azure. Prior understanding of Azure architecture and services is necessary. Some knowledge of DevOps principles and techniques will be useful.